EVALUASI PENATAUSAHAAN, PENYUSUNAN, DAN PENYAMPAIAN LAPORAN PERTANGGUNGJAWABAN BENDAHARA PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN MALUKU TENGGARA BARAT - Lewedalu, Grace G; Kalangi, Lintje; Warongan, Jessy D. L. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
The activities of the financial administration has an interest in controlling the implementation of the budget and expenditure, given their authorization has been granted by the determination to the local regulations and approval by the competent authority. It is closely linked with the principal task of Treasurer in trust by the employer to manage, store and account for its report in accordance with applicable regulations. Minister of the Interior issued a regulation that Minister Regulation number 55 of 2008 on Procedures for Administration and Treasurer Accountability Report Preparation and Transmission. This rule also applies to the Treasurer on the Financial Management Board and Assets West Southeast Maluku District. The research objective was to evaluate the accountability report of the treasurer is in conformity with applicable regulations. Data analysis method used is the method of descriptive data analysis, by analyzing, managing and comparing the data with that obtained both qualitative and quantitative in its application research results illustrate the particular Agency Financial Management and Asset West Southeast Maluku District has shown good performance and according to the rules regulation No. 55 of 2008. Head of BPKAD as PPKD, BUD, PA, should do even more stringent supervision so that the accountability reports are included in BPKAD can be run in accordance with applicable regulations. Keywords: Administration, Formulation, Submission, Accountability Report, treasurer